Detection of West Nile virus in wild birds in Tana River and Garissa Counties, Kenya - Nyamwaya, D.; Wang'ondu, V.; Amimo, Joshua O.; Michuki, George N.; Ogugo, M.; Ontiri, E.; Sang, R.; Lindahl, Johanna F.; Grace, Delia; Bett, Bernard K. (Springer, 2016)
Background West Nile fever virus is a zoonotic arboviral infection maintained in a sylvatic cycle involving mosquito vectors and birds. It is one the arboviruses whose geographical range is expanding because of climate and land use changes that enhance the densities of mosquitoes and promote mosquito-bird-human interactions. We carried out a survey to determine the reservoirs of WNV among wild birds in Tana River and Garissa counties, Kenya. Methods Blood samples were obtained from 361 randomly trapped wild birds. Using real-time polymerase chain reaction (PCR), all samples were screened for WNV using gene specific primer sets amplifying a portion of the E region of the genome encoding the envelope protein. Results Sixty five (65) out of 361 birds screened tested positive for WNV on real-time PCR assay. Sequencing of the selected positive samples reveals that the isolated WNV were most closely related to strains isolated from China (2011). A regression analysis indicated that sampling location influenced the occurrence of WNV while species, age, weight and sex of the birds did not have any effect. Conclusions This study provides baseline information on the existing circulation of WNV in this region among wild bird reservoirs that could spill over to the human population and points to the need for implementation of surveillance programs to map the distribution of the virus among reservoirs. Awareness creation about West Nile fever in this region is important to improve its detection and management.